Genetic and phenotypic parameters for growth traits of Sonadi sheep - SHARMA, PRAKASH CHANDRA; MEENA, RUHI; KUMAR, SUNIL (The Indian Journal of Animal Sciences, 2022)
The aim of present study was to estimate the genetic and phenotypic parameters for growth traits of Sonadi sheep. Records of lambs were collected over a period of four years from Sonadi unit maintained at CVAS Navania (Rajasthan) under Mega Sheep Seed Project. Traits included for the study were birth weight (BWT), weight at three months (3MWT), weight at six months (6MWT), weight at nine months (9MWT) and weight at twelve months of age (12MWT). Low estimates of heritability were observed for weight at birth, three and twelve months of age. Lamb weight at six and nine months of age was moderately heritable and shows that these traits are less influenced by environmental effects; which make them effectively transmitted to the progeny. However, estimates of genetic parameter with high sampling error do not agree with empirical results. The direct maternal genetic correlation (ram) was negative for all body weight except for twelve months body weight. A negative estimate of ï³am resulted in increase in direct and maternal heritability pointing towards cross substitution effect in the partitioning of total variation. The high positive genotypic and phenotypic correlations between body weight at six months, nine months and twelve months of age indicates that selection for six months of traits will result in increase in nine and twelve months of body weight